2019
DOI: 10.1111/ejn.14654
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in head‐fixed voluntary running behavior in C57BL/6J mice

Abstract: Sex differences in running behaviors between female and male mice occur naturally in the wild. Recent experiments using head‐fixed mice on a voluntary running wheel have exploited analogous locomotor activity to gain insight into the neural underpinnings of a number of behaviors ranging from spatial navigation to decision‐making. It is however largely unknown if sex differences exist between females and males in a head‐fixed experimental paradigm. To address this, we characterized locomotor activity in head‐fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The purpose of these sessions was to acclimate the mice to running on a wheel while head fixed. We previously found that following 5 days of exposure, both male and female mice habituate to the run wheel based on their running behavior (36) after which electrophysiology was performed.…”
Section: Run Wheel Habituationmentioning
confidence: 99%
“…The purpose of these sessions was to acclimate the mice to running on a wheel while head fixed. We previously found that following 5 days of exposure, both male and female mice habituate to the run wheel based on their running behavior (36) after which electrophysiology was performed.…”
Section: Run Wheel Habituationmentioning
confidence: 99%
“…Sex is a critical biological variable and should be considered in study design ( Shansky, 2019 ). In a previous study of head-fixed wheel running similar to the task used in this experiment, it was found that female animals behaved differently on a run wheel, including how they adapted and habituated to the wheel while being head fixed ( Warner and Padmanabhan, 2020 ). These sex differences may be related to anxiogenic behaviors, and could influence activity patterns in ventral CA1, as has been previously shown ( Ciocchi et al, 2015 ; Jimenez et al, 2018 ).…”
Section: Discussionmentioning
confidence: 98%
“…During the 7-d period immediately following head frame implantation, animals were habituated to the virtual reality environment ( Warner and Padmanabhan, 2020 ). Mice were head-fixed in the virtual environment and allowed to run for 1 h each day.…”
Section: Methodsmentioning
confidence: 99%
“…During the 7-day period immediately following head frame implantation, animals were habituated to the virtual reality environment (Warner and Padmanabhan, 2020). Mice were head-fixed in the virtual environment and allowed to run for one hour each day.…”
Section: Star Methodsmentioning
confidence: 99%